The holistic curriculum - Miller, John P., 1943- (Toronto : University of Toronto Press, 2008)
Holistic education is concerned with connections in human experience - connections between mind and body, between linear thinking and intuitive ways of knowing, between individual and community, and between the personal self and the transpersonal self. First published in 1988, The Holistic Curriculum examines the philosophical, psychological, and social foundations of holistic education, outlining its history and discussing practical applications in the classroom. This revised and expanded second edition concisely describes how holistic thinking integrates spiritual and scientific perspectives, drawing on romantic, humanistic, and other radical alternatives to the atomistic worldview of the modern age. The role of the teacher, the issue of accountability, and strategies for implementing the Holistic Curriculum are also discussed.
Keywords: Holisme ; onderwijs